Inventário portage operacionalizado: uma proposta de adaptação para crianças com baixa visão - Quintão, Cassiana Saraiva (2020)
In Brazil, there is a lack of instruments to assess the development of children with visual impairment. On the other hand, the country counts on the Operationalized Portage Inventory (OPI) adapted to the Brazilian reality whose objective is to raise the development repertoire of children from 0 to 6 years old. The OPI consists of 580 items, organized into six areas. This work aims to describe two stages of the OPI adaptation process for children with low vision. The first step was the selection and modification of the items that would be adapted by a Committee of Experts. Three professionals took part in this stage, experts in child development, visual impairment and the operationalization of the OPI, denominated “specialists”. Each specialist read all items and recorded aspects of each item that required modification. The three experts presented their positions and arguments about the need to modify each item and still their consensus on the need to adapt each item examined. In case of doubts regarding the direction of adaptation, the description of the item's teaching activities was consulted in the Portage Guide, in the Spanish version that one of the specialists had available. In cases of persistent doubt, the original formulation of the item was preserved. In order to assess their agreement with the OPI items by area, it was established in a meeting that for each area the minimum agreement rate would be 90%. In this first stage the results indicated that 42.75% (248) of the 580 items should be adapted. In relation to the areas, there was a need to adapt to: Child Stimulation = 42.22% (19); Socialization = 31.32% (26); Cognition = 65.7% (71); Language = 53.53% (53); Self-care = 15.23% (16) and Motor Development = 44.41% (63). The changes proposed by the specialists focused on the components of each item: material, condition, criteria and / or response. To guide the applicators to evaluate the items, a general instruction was elaborated to inform the applicator about important aspects for the performance of people with low vision, such as visual field preferences, perception of contrasts, preference for lighting and visual discrimination. In the second stage of the study, three independent expert judges were invited to assess the theoretical coherence of the 1st version of the OPI-BV proposed by the Committee of Experts. One judge was expert in visual impairment, and the others in Child development and psychological instruments preparation, respectively. The judges received a general instruction and six protocols containing the 248 items in their original versions and modified by the Committee of Experts, with a two-month deadline for returning the material. The judges were free to contact the researcher in case of doubts during the analysis. Independently, the three judges made adjustments on different items and their components, totalizing 419 suggestions. The analysis of the judges' nominations was made by the Committee of Experts, which decided to re-elaborate only the items in which there was unanimous agreement in the indication of adjustments, regardless of whether or not it was in the same component. Two categories were developed with criteria for accepting or not the judges' suggestions. In the 1st category it was agreed that suggestions would be taken to make the stimuli more visible and the material more noticeable (visual and / or auditory). Suggestions related to improvements in the condition component, improvements in the elaboration of the wording, and related general suggestions in the item would not be accepted, as well as complicated suggestions that contradicted the original version of the OPI and also contradictions between the judges´suggestions in the same item and components or in different items and components. In addition to the judges' work, a low vision specialist offered contributions that were considered for the changes. The work carried out in the second stage resulted in the insertion of the three judges´contributions to the 22 items for which there was agreement, and in the insertion of the low vision (orthopedist) specialist´s contributions towards the General Instruction for applicators, Specific Instructions and guidelines about the distance in which objects are located and fixed, identification of the visual field of preference, visual discrimination or better use of vision and tips to improve contrast. The 22 items were analyzed and the suggestions were incorporated, according to the two categories of analysis created by the Committee of Experts. Thus, this work resulted in drawing up the 2nd Version of the OPI-BV, consisting of the 332 items of the OPI original version which haven´t been modified, plus the 248 items modified by the Committee of Experts, including the 22 that were reworked by taking into account the expert judges´ recommendations and also a new General Instruction and Specific Instructions with the changes suggested by the visual impairment specialist (orthopedist). The conclusion is that the participation of expert judges brought positive contributions to adaptating the OPI to the brazilian reality and even made it possible to improve the items in order to elaborate the OPI 2nd version for children with low vision.